Pengajaran apresiasi sastra Indonesia di perguruan tinggi terbuka dan jarak jauh - Rusyana, Enang; Prakoso, Teguh (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
Teaching literature equips learners with the knowledge and skills of appreciating literary works. Learners are expected to be able to feel and enjoy the beauty of literary works. Teaching literary appreciation still experiences obstacles due to limited time allocation and teacher skills. Such constraints occur in face-to-face teaching of literature appreciation, and are likely to occur in open and distance learning. It is very interesting to study considering that teachers and students in open and distance learning do not meet face-to-face in the classroom. This article describes the teaching of Indonesian literature appreciation in open and distance education. The method used is descriptive qualitative. Data were collected from the subject matter books of PBIN 4213 Poetry, PBIN 4217 Drama, and PBIN 4219 Teaching Literary Appreciation, as well as archives of their teaching implementation at the Universitas Terbuka. The teaching materials from the three subject matter books were analyzed and juxtaposed with the teaching process delivered through asynchronous online tutorials. The results of the analysis show that teaching Indonesian literature appreciation can be implemented in open and distance universities through online tutorials.